Stressed individual's preferences for outdoor activities in urban parks / Nor Izana Mohd Shobri, Norhafizah Abdul Rahman and Md Saman Nor Hisham - Mohd Shobri, Nor Izana; Abdul Rahman, Norhafizah; Nor Hisham, Md Saman (2021)
Outdoor activities in urban public park environments play critical roles in reducing stress levels or at least mental fatigue, of the urban dwellers. Although the importance of planning and designing of urban parks that possess the right and appropriate outdoor activities are well acknowledged, they receive inadequate attention from researchers. Cognizance of the above offset, this paper intends to enrich the current debate and criteria or factors of outdoor activities from the users' perspectives. To do that, this paper employs Kuala Lumpur inhabitants as a case study and respondents. An investigation is made to identify the preferences of outdoor activities by stressed individuals. The quantitative approach through a web-based questionnaire was employed in this study. A pilot study that involves a total of 62 respondents of the Kuala Lumpur population was used as a basis of the investigation. As an exploratory study, at least at this stage, the data have been analyzed using the descriptive statistics or to be specific via mean analysis. It was observed that the level of preferred outdoor activities positively relates to individual stress levels. This paper provides fresh and novel insights into the factors that need to be taken by landscape architects, planners, urban parks managers, architects, and alike in planning and designing the functional urban parks.